STUDI TEKNOLOGI PUKAT TERI (PURSE SEINE) DI DESA KWALA GEBANG KECAMATAN GEBANG KABUPATEN LANGKAT PROVINSI SUMATERA UTARA - Rengi, Pareng; Brown, Arthur; ', Nurkhaira (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted on January 2016 at Kwala Gebang village, Gebang sub district, Langkat district, Sumatera Utara province with the aim to know general construction, environmentally friendly, and business profitability of pukat teri. This research is survey methods. The results showed that pukat teri construction same with purse seine and included in environmentally friendly fishing gear. Pukat teri of financially suitability developing which is BCR value is 1,14 with the value of FRR (31,97 %) higher than the bank rate (6,50 %). The value of PPC (payback period of capital) is 3,12Keywords : Pukat Teri, Environmentally Friendly, Financial Analysis, Kwala Gebang Village.